Week 3 Discussion Notes

Table of Contents

Induction

Example 1.

Prove 13+23++n3=(1+2++n)21^3 + 2^3 + \cdots + n^3 = \p{1 + 2 + \cdots + n}^2 for all positive integers nn.

Solution.

Base case: (n=1n = 1) Plugging n=1n = 1 into the left side, we get

13=1=12,1^3 = 1 = 1^2,

so the base case holds.

Inductive step: Suppose the equation is true for n=kn = k, i.e., assume that

13+23++k3=(1+2++k)21^3 + 2^3 + \cdots + k^3 = \p{1 + 2 + \cdots + k}^2

is true. We need to show that it's true for n=k+1n = k + 1:

(1+2++k+(k+1))2=((1+2++k)+(k+1))2=(1+2++k)2+2(k+1)(1+2++k)+(k+1)2=(13+23++k3)+2(k+1)k(k+1)2+(k+1)2=(13+23++k3)+k(k+1)2+(k+1)2=(13+23++k3)+(k+1)2(k+1)=13+23++k3+(k+1)3,\begin{aligned} \p{1 + 2 + \cdots + k + \p{k + 1}}^2 &= \p{\p{1 + 2 + \cdots + k} + \p{k + 1}}^2 \\ &= \p{1 + 2 + \cdots + k}^2 + 2\p{k + 1}\p{1 + 2 + \cdots + k} + \p{k + 1}^2 \\ &= \p{1^3 + 2^3 + \cdots + k^3} + 2\p{k + 1} \cdot \frac{k\p{k + 1}}{2} + \p{k + 1}^2 \\ &= \p{1^3 + 2^3 + \cdots + k^3} + k\p{k + 1}^2 + \p{k + 1}^2 \\ &= \p{1^3 + 2^3 + \cdots + k^3} + \p{k + 1}^2\p{k + 1} \\ &= 1^3 + 2^3 + \cdots + k^3 + \p{k + 1}^3, \end{aligned}

so the inductive step holds. Thus, by induction, the formula is true for all positive integers.

Example 2.

Prove 7n6n17^n - 6n - 1 is divisible by 3636 for all positive integers nn.

Solution.

To make things easier to write, I'll be writing 36k36 \mid k to mean "3636 divides kk".

Base case: (n=1n = 1) When n=1n = 1, we get

7161=0,7^1 - 6 - 1 = 0,

and 3636 divides 00, so the base case holds.

Inductive step: Assume 7k6k17^k - 6k - 1 is divisible by 3636. We need to show that 7k+16(k+1)17^{k+1} - 6\p{k + 1} - 1 is also divisible by 3636:

7k+16(k+1)1=77k6k61=(6+1)7k6k61=67k6+(7k6k1)=6(7k1)+(7k6k1).\begin{aligned} 7^{k+1} - 6\p{k + 1} - 1 &= 7 \cdot 7^k - 6k - 6 - 1 \\ &= \p{6 + 1} \cdot 7^k - 6k - 6 - 1 \\ &= 6 \cdot 7^k - 6 + \p{7^k - 6k - 1} \\ &= 6 \cdot \p{7^k - 1} + \p{7^k - 6k - 1}. \end{aligned}

Since 36(7k6k1)36 \mid \p{7^k - 6k - 1}, there exists mZm \in \Z such that 7k6k1=36m7^k - 6k - 1 = 36m. Rearranging, this also tells us that 7k1=36m+6k7^k - 1 = 36m + 6k, so

7k+16(k+1)1=6(7k1)+(7k6k1)=6(36m+6k)+36m=36(6m+1)+36m,\begin{aligned} 7^{k+1} - 6\p{k + 1} - 1 &= 6 \cdot \p{7^k - 1} + \p{7^k - 6k - 1} \\ &= 6 \cdot \p{36m + 6k} + 36m \\ &= 36 \cdot \p{6m + 1} + 36m, \end{aligned}

which means 36(7k+16(k+1)1)36 \mid \p{7^{k+1} - 6\p{k + 1} - 1}. By induction, this is true for all positive integers.

Rational Numbers Q\Q

Theorem (rational roots theorem)

Consider the equation

cnxn+cn1xn1++c0=0,c_n x^n + c_{n-1} x^{n-1} + \cdots + c_0 = 0,

where c0,c1,,cnZc_0, c_1, \ldots, c_n \in \Z. Let r=cdr = \frac{c}{d} be a rational solution to the equation, where rr is simplified so that cc and dd have no factors in common. Then cc is a factor of c0c_0 and dd is a factor of cnc_n.

The intuition for the proof is as follows: cd\frac{c}{d} is a root of dxcdx - c, so we want to factor the polynomial into

cnxn+cn1xn1++c0=(dxc)(an1xn1++a0)=dan1xn+ca0.\begin{aligned} c_n x^n + c_{n-1} x^{n-1} + \cdots + c_0 &= \p{dx - c}\p{a_{n-1}x^{n-1} + \cdots + a_0} \\ &= da_{n-1} x^n + \cdots - ca_0. \end{aligned}

If we compare coefficients, we see cn=dan1c_n = da_{n-1} and ca0=c0-ca_0 = c_0, so if an1a_{n-1} and a0a_0 are integers, then dd should divide cnc_n and cc should divide c0c_0. We can't guarantee that an1a_{n-1} and a0a_0 are integers, though, so this isn't a proof.

Corollary

If pp is a prime and n2n \geq 2 is a positive integer, then pn\sqrt[n]{p} is irrational.

Proof.
(Sketch)

Consider the equation

xnp=0.x^n - p = 0.

Write out all the possible rational solutions and show that none of them are actually solutions. (Recall that 11 is not a prime.) \square

Real Numbers R\R

Definition

One problem with Q\Q is that it has lots of gaps. For example, you can "separate" Q\Q into

Q={qQq2<2}{qQq2>2},\Q = \set{q \in \Q \mid q^2 < 2} \cup \set{q \in \Q \mid q^2 > 2},

i.e., Q\Q "jumps over" 2\sqrt{2}. This is why we want to work with the real numbers; it has no gaps.

Definition (the real numbers)

The real numbers, denoted R\R, is the ordered field with the least upper bound property.

In other words, R\R is what you "expect it to be":

  • Ordered means you can compare two numbers, i.e., they're equal or one is bigger than the other.
  • Field means you can add, subtract, multiply, and divide like you always did.

The least upper bound property takes a bit more work to understand.

The Least Upper Bound Property

Definition

Let SRS \subseteq \R. Then

  • SS is bounded above if there exists BRB \in \R such that xS\forall x \in S, xBx \leq B. We call BB an upper bound for SS.
  • SS is bounded below if there exists LRL \in \R such that xS\forall x \in S, LxL \leq x. We call LL a lower bound for SS.
  • SS is bounded if it is both bounded above and bounded below.
Example 3.

If a,ba, b are finite, then:

  • (,b)\p{-\infty, b} is bounded from above (by bb) but not from below,
  • (a,)\p{a, \infty} is bounded from below (by aa) but not from above,
  • (a,b)\p{a, b} is bounded.

Now we can understand what the least upper bound property is:

Definition

R\R has the least upper bound property, that is:

If SRS \subseteq \R is non-empty and bounded above, then there exists xRx^* \in \R such that:

  1. xx^* is an upper bound for SS, and
  2. if BB is another upper bound for SS, then xBx^* \leq B.

When this happens, we call xx^* the supremum of SS and write x=supSx^* = \sup{S}.

The least upper bound is what it sounds like: it's an upper bound that's smaller than any other upper bound.

Proposition

If supS\sup{S} exists, then it is unique.

Proof.

Suppose x,xx, x' are two least upper bounds for SS.

  • Since xx is a least upper bound and xx' is another upper bound for SS, we get xxx \leq x'.
  • Similarly, xx' is a least upper bound and xx is an upper bound for SS, so xxx' \leq x.

Putting these together, we get x=xx = x'. \square

Example 4.

If a<ba < b and bb is finite, then sup(a,b)=b\sup{\p{a, b}} = b. Here, aa is allowed to be -\infty.

Solution.

To show that bb is the least upper bound, we need to show:

  1. it is an upper bound, and
  2. if MM is another upper bound for (a,b)\p{a, b}, then bMb \leq M.

By definition, if x(a,b)x \in \p{a, b}, then a<x<ba < x < b, so bb is an upper bound for (a,b)\p{a, b}, which proves (1).

We'll prove (2) by contradiction: assume that MM is another upper bound for (a,b)\p{a, b}, but M<bM < b. There are two cases:

Case 1: If a=a = -\infty, then M(,b)M \in \p{-\infty, b}.

Case 2: If aa is finite, then a+b2(a,b)\frac{a + b}{2} \in \p{a, b}. By definition of upper bound, a+b2M\frac{a + b}{2} \leq M, so

a<a+b2M<b,a < \frac{a + b}{2} \leq M < b,

so M(a,b)M \in \p{a, b}.

In either case, M(a,b)M \in \p{a, b}, but this means that M+b2(a,b)\frac{M + b}{2} \in \p{a, b}, so

M<M+b2<b,M < \frac{M + b}{2} < b,

a contradiction. Thus, bMb \leq M to begin with, which completes the proof.

Definition

We say that R\R has the greatest lower bound property if:

Whenever SRS \subseteq \R is non-empty and bounded below, there exists xRx_* \in \R such that:

  1. xx_* is a lower bound for SS, and
  2. if LL is another lower bound for SS, then LxL \leq x_*.

In this case, we say xx_* is the infimum of SS, and we write x=infSx_* = \inf{S}.

Proposition

R\R has the greatest lower bound property.

Proof.

The closest thing we have to this is the least upper bound property, so we want to try to use it somehow.

The idea is try to reverse engineer what the greatest lower bound for SS would be. If we "mirror" SS, i.e., consider the set S={xxS}-S = \set{-x \mid x \in S}, then we get something like this:

Based on this picture, infS\inf{S} should correspond to sup(S)\sup\,\p{-S} after the reflection. Since SS \neq \emptyset, this tells us that S-S \neq \emptyset also. We also know that SS is bounded below, so let LL be a lower bound for SS. Then given xS-x \in S,

Lx    xL,L \leq x \implies -x \leq -L,

so L-L is an upper bound for S-S, i.e., S-S is bounded from above. By the least upper bound property, sup(S)\sup\,\p{-S} exists.

Based on the picture, we will try to prove that infS=sup(S)\inf{S} = -\sup\,\p{-S}. As before, there are two things to prove:

  1. sup(S)-\sup\,\p{-S} is a lower bound for SS, and
  2. if LL is another lower bound for SS, then Lsup(S)L \leq -\sup\,\p{-S}.

To show (1), let xSx \in S. Then xS-x \in -S, so by definition of the supremum,

xsup(S)    sup(S)x.-x \leq \sup\,\p{-S} \implies -\sup\,\p{-S} \leq x.

Since xx was arbitrary, this means sup(S)-\sup\,\p{-S} is a lower bound for SS.

To show (2), let LL be another lower bound for SS. Then by the same argument as before, L-L is an upper bound for S-S, so by the least upper bound property,

sup(S)L    sup(S)L.\sup\,\p{-S} \leq -L \implies -\sup\,\p{-S} \leq L.

Thus (2) holds, so infS=sup(S)\inf{S} = -\sup\,\p{-S}. \square

Exercise 1.

Prove that if infS\inf{S} exists, then it is unique.

Example 5.

If a,ba, b are real numbers such that aa is finite and a<ba < b, then inf(a,b)=a\inf{\p{a, b}} = a.

Solution.

In our proof of the greatest lower bound property, we showed that infS=sup(S)\inf{S} = -\sup\,\p{-S}. Applying this with S=(a,b)S = \p{a, b}, we get

inf(a,b)=sup(b,a)=(a)=a.\inf{\p{a, b}} = -\sup\,\p{-b, -a} = -\p{-a} = a.